Parametric Studies Into Creep and Shrinkage Characteristics in Railway Prestressed Concrete Sleepers - Li, Dan; Kaewunruen, Sakdirat; Robery, Peter; Remennikov, Alex M. (Frontiers in Built Environment, 2020)
Prestressed concrete is very suitable for railway sleepers because of its many superior advantages in high performance, maintenance, sustainability, and construction. Prestressed concrete improved the structural performance which has stronger tensile resistance in comparison with common concrete. However, the long-term performance largely depends on creep and shrinkage responses. The effects of time-dependent phenomena on prestressed concrete sleeper are investigated. In the past, many investigators have proposed various material models to predict creep and shrinkage but those were mostly based on general reinforced concrete concept. The popular uses of prestressed concrete have led to a concern of practitioners whether those existing predictive models could be realistically applied to prestressed concrete. Due to high initial elastic shortening in prestressed concrete, the creep and shrinkage effects should be critically re-evaluated in flexural members. This study investigates and compares the effects of creep and shrinkage on railway prestressed concrete sleepers. The comparison between prediction models underpinned by European Standard Eurocode 2, American Standard ACI, and Australian Standard AS3600-2009 provides the new insight into the time-dependent performance of concrete sleepers installed in various locations. The outcome of this study will help rail track engineers to better design and maintain railway infrastructure, improving asset management efficacy.